Life satisfaction during temporary housing after an earthquake: Comparing three cases in Italy. (1st June 2023) - Di Bucci, D.; Del Missier, F.; Dolce, M.; Galvagni, A.; Giordano, F.; Patacca, A.; Pezzi, E.; Scurci, G.; Savadori, L.
Abstract: A disaster has a considerable impact on people who have lost their homes. We analyzed the life satisfaction of displaced people accommodated in temporary housing after three strong earthquakes that occurred in Italy in 2009 (Abruzzo), 2012 (Emilia), and 2016–17 (Central Italy). Information was obtained through an anonymous survey on a large number of variables related to socio-demographic features, temporary housing type and quality, social support and protection network, personal psychological resources and preparedness, and psychophysical health. Responses were collected through face-to-face and telephone interviews, stand-alone paper-and-pencil questionnaires, or online (N = 261). In the whole-sample analysis, the significant predictors of life satisfaction were earthquake preparedness, which earthquake out of three was experienced, protection network, accommodation type and quality, and general health status, thus highlighting the complex and multi-faceted nature of the underpinnings of life satisfaction in people displaced after an earthquake. However, different predictors explained life satisfaction in the analysis of each earthquake, pointing to the need to consider their specificity and the local context. Nevertheless, the perceived quality of the accommodation was a significant predictor both in the whole-sample analysis and in the analysis of two earthquakes (2009 Abruzzo and 2012 Emilia), highlighting the importance of providing temporary houses with appropriate properties (privacy, space, thermal and acoustic insulation, light, quality of materials, surroundings) and placed in locations that allow the resumption of life activities (e.g., education, work, socialization, health and public facilities and services). Highlights: Life satisfaction during temporary housing after three earthquakes was investigated. Perceived quality of the temporary accommodation predicted life satisfaction. Preparedness, protection network, and health status were additional predictors. The importance of different predictors varied from case to case. Improving satisfaction during displacement may require different kinds of actions.